2022
DOI: 10.3847/1538-4357/ac7f33
|View full text |Cite
|
Sign up to set email alerts
|

Observing Scenarios for the Next Decade of Early Warning Detection of Binary Neutron Stars

Abstract: We describe representative observing scenarios for early warning detection of binary neutron star mergers with the current generation of ground-based gravitational wave detectors as they approach design sensitivity. We incorporate recent estimates of the infrastructure latency and detector sensitivities to provide up-to-date predictions. We use Fisher analysis to approximate the associated localizations, and we directly compare to Bayestar to quantify biases inherited from this approach. In particular, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…In this paper, we use the Fisher matrix method, which is based on a linear approximation around the maximum likelihood and could forecast parameter errors in GW detection very simply and quickly. Recently, the reliability of the Fisher matrix method has been widely discussed (Vallisneri 2008;Rodriguez et al 2013;Grover et al 2014;Iacovelli et al 2022;Magee & Borhanian 2022;Gardner et al 2023). They found that at low S/Ns, as the linear approximation no longer holds, the likelihood function deviated from the Gaussian distribution.…”
Section: Gaussian Likelihood Approximationmentioning
confidence: 99%
“…In this paper, we use the Fisher matrix method, which is based on a linear approximation around the maximum likelihood and could forecast parameter errors in GW detection very simply and quickly. Recently, the reliability of the Fisher matrix method has been widely discussed (Vallisneri 2008;Rodriguez et al 2013;Grover et al 2014;Iacovelli et al 2022;Magee & Borhanian 2022;Gardner et al 2023). They found that at low S/Ns, as the linear approximation no longer holds, the likelihood function deviated from the Gaussian distribution.…”
Section: Gaussian Likelihood Approximationmentioning
confidence: 99%
“…For example. future detectors could determine the NS equation of state (e.g., Coupechoux et al 2023), can provide early warning detections of NSNS mergers (e.g., Magee & Borhanian 2022), provide improved sky localization allowing for more multimessenger observations (e.g., Mills et al 2018;Petrov et al 2022), might be able to observe the existence of BHs before star formation took place Note. The acronyms are: Einstein Telescope (ET), Cosmic Explorer (CE), a network of four A+ sensitivity detectors here consisting of LIGO-Hanford (H), LIGO-Livingston (L), KAGRA (K), and LIGO-India (I) , two CE-like detectors (2CE) and a network of three next-generation detectors consisting of ET, CE, and CE-South (ECS), and not applicable (N/A; the authors did not mention rates for this flavor).…”
Section: Future Outlook: Beyond Detector Numbersmentioning
confidence: 99%
“…Early detection and localization of BNS are therefore of great importance in GW astronomy. It has previously been demonstrated that there is a nonzero probability of detecting and localizing premerger BNS events with current (Magee et al 2021;Kovalam et al 2022) and near-future (Nitz et al 2020;Sachdev et al 2020;Banerjee et al 2023;Magee & Borhanian 2022) GW observatories, typically within seconds to 1 minute before merger. Chaudhary et al (2023) has recently investigated early warning for the fourth observing run of LIGO-Virgo-KAGRA collaboration, with multiple detection pipelines already equipped for early-warning searches (Messick et al 2017;Nitz et al 2018;Aubin et al 2021;Chu et al 2022).…”
Section: Introductionmentioning
confidence: 99%